Criminal justice system involvement and continuity of youth crime: a longitudinal test of labeling theory - Johnson, Lee Michael (2001)
Adolescent crime is a major issue confronting not only the criminal justice system and the general public, but researchers as well. Studies of criminal careers reveal several possible factors explaining persistent offending. At one time, labeling theory was a popular explanation for continued deviance, but a lack of empirical support and conceptual objections soon made the theory unpopular. In this analysis, labeling theory is integrated with other theories and then re-considered as an explanation for persistent youth crime. The primary contention here is that formal legal sanctioning---in the form of involvement with the police, courts, and correctional agencies---may, ironically, operate as a factor sustaining persistent offending. Seven waves of data collected on 153 males were used to test a model hypothesizing relationships among criminal justice system involvement, association with deviant peers, and crime---over time. Results revealed continuity in offending across waves, but only partial continuity in deviant peer association. More importantly, consistent with labeling theory, criminal justice system involvement was positively related to later crime, as well as to later deviant peer association. Further, crime was positively related to later deviant peer association, but deviant peer association was not related to later crime, and same-time correlation between the two were significantly positive. While, understandably, crime predicted criminal justice system involvement, deviant peer association did not. Based on these results, labeling processes should be viewed within a life course perspective, and implications for theory, research, and treatment are discussed